Clinical and laboratory features of childhood systemic lupus erythematosus and its course in Department of Child Health, Cipto Mangunkusumo Hospital, Jakarta - Zakiudin Munasir; Tuty Mariana; Rulina Suradi (Indonesian Pediatric Society, 2001)
A descriptive, retrospective study has been performed among 33 children with SLE during the period of January 1986 to December 1999 in Department of Child Health, Cipto Mangunkusumo Hospital. The results of the present study show that SLE in childhood was more commonly found in girls than in boys, with a ratio of 4.5: 1. The mean age of onset was 10.5 years and the mean age of diagnosis was 10.9 years, most frequently observed in the age of > 10 years and rarely found in the age of < 5 years. The time interval between the time of onset and time of diagnosis ranged from 1 to 24 months and the most frequent interval was 1-3 months. The most common initial symptoms were prolonged fever, rash on the skin and face, and athralgia. In its natural history of the disease, kidneys, skin/mucous membrane and joints are the most frequent organs involved. Most of the SLE patients develop anemia. Positive anti ds-DNA, ANA and decreased levels of C3 and C4 respectively in 28 (28/31), in 29 (29/30), in 25 (25/33), and in 19 (19/27) cases. LE cells were encountered only in four (4/17) cases. Â Out of 11 cases upon which renal biopsies were done, the most common histological features were mesangeal glomerulonephritis (class II) and diffuse proliferative glomerulonephritis (class IV). The mean time interval between the onset and renal complication manifestations was 6.96 months, cardiac complication was 16.77 months, central nerve system was 22.71 months and lungs were 25.0 months. Duration of illness of patients with SLE ranged from 2 to 175 with the mean of 31.3 months. The causes of death were mostly due to gastrointestinal bleeding and renal failure.